Anaesthetic management of a patient with morbid obesity: case report - Arop M. D. Kual; Nkhabe Chinyepi; Katlo Rainy Diane; Karabo Ngwako; Rashid Lwango (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2021)
The purpose of this case report is to describe our experience of the anaesthetic management of a patient with morbid obesity undergoing general surgery. The obese patient is at great risk of problems with endotracheal intubation and developing peri-operative respiratory and cardiovascular complications. The difficulties in moving and positioning the patient and gaining venous access add to the problems. Anaesthesia and surgery on an obese patient should not be undertaken lightly without a full understanding of the potential problems.